The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1128/jb.00416-22
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Two-Component Systems in Coxiella burnetii Reveals Redundant Regulatory Schemes and a Requirement for an Atypical PhoBR System in Mammalian Cell Infection

Abstract: C. burnetii is an obligate intracellular bacterium with a spore-like stability allowing it to survive long periods of time in the environment. This stability is likely due to its biphasic developmental cycle, whereby it can transition from an environmentally stable small-cell variant (SCV) to a metabolically active large-cell variant (LCV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…CRISPRi has provided inducible knockdown of gene expression and enabled genetic approaches to study essential gene function in several bacterial pathogens ( 51 53 ). Only a handful of studies have reported the use of CRISPRi in intracellular bacteria ( 22 , 54 , 55 ). We have demonstrated successful knockdown of topA in C. trachomatis using a plasmid-based CRISPRi system that relies on the combination of inducible dCas12 and a topA -specific crRNA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPRi has provided inducible knockdown of gene expression and enabled genetic approaches to study essential gene function in several bacterial pathogens ( 51 53 ). Only a handful of studies have reported the use of CRISPRi in intracellular bacteria ( 22 , 54 , 55 ). We have demonstrated successful knockdown of topA in C. trachomatis using a plasmid-based CRISPRi system that relies on the combination of inducible dCas12 and a topA -specific crRNA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPRi has provided inducible knockdown of gene expression and enabled genetic approaches to studying essential gene function in several bacterial pathogens (49-51). Only a handful of studies have reported the use of CRISPRi in intracellular bacteria (20, 52, 53). We have demonstrated successful knockdown of topA in C. trachomatis using a plasmid-based CRISPRi system that relies on the combination of inducible dCas12 and a topA -specific crRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results imply disparities in the responses of C. trachomatis to the sub-MIC of Mox between L2/topA-kd, L2/Nt, and L2/topA-kd, suggesting that the levels of topA expression influences the chlamydial response to moxifloxacin. Only a handful of studies have reported the use of CRISPRi in intracellular bacteria (20,52,53) . We have demonstrated successful knockdown of topA in C. trachomatis using a plasmid-based CRISPRi system that relies on the combination of inducible dCas12 and a topA-specific crRNA.…”
Section: Targeted Topa Knockdown Affects the Response Of C Trachomati...mentioning
confidence: 99%